2015
DOI: 10.1177/0040517515569525
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a color matching algorithm for digital transfer textile printing using an artificial neural network and multiple regression

Abstract: A color matching algorithm has been developed to solve the color mismatch problems encountered during the digital transfer textile printing process. To match the colors between display and fabric, standard red, blue, green (sRGB) and International Commission on Illumination (CIE) color systems were used. For an affordable color matching process, sRGB values of printed fabric were extracted by a general flatbed scanner instead of an expensive spectrophotometer. Extracted sRGB values and originally intended targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…To find the color differences, the spot color should be covered to standard red, blue and green (sRGB) color values. 37 Then the CIE XYZ value can be calculated by using the sRGB values according to the following equation …”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find the color differences, the spot color should be covered to standard red, blue and green (sRGB) color values. 37 Then the CIE XYZ value can be calculated by using the sRGB values according to the following equation …”
Section: Experiments and Resultsmentioning
confidence: 99%
“…To find the color differences, the spot color should be covered to standard red, blue and green (sRGB) color values. 37 Then the CIE XYZ value can be calculated by using the sRGB values according to the following equation X Y Z Finally, the CIE Lab color value can be obtained by a nonlinear transformation of the CIE XYZ color value, as shown in the following equation…”
Section: Recipes With Three and More Primary Colorsmentioning
confidence: 99%
“…As is widely recognized, 16 ANNs are computational systems that simulate the microstructure of a biological nervous system. ANNs can be trained to perform a particular function, either from information from outside the network or by the neurons themselves in response to the input.…”
Section: Artificial Neural Network Training and Prediction Of The Blementioning
confidence: 99%
“…The obtained results were shown that the reverse characterization model based on neural network has more accuracy. Hwang et al introduced a color matching algorithm for digital transfer textile printing using an artificial neural network and multiple regression. For this purpose, sRGB values of printed fabric were obtained by a flatbed scanner.…”
Section: Introductionmentioning
confidence: 99%